FIRST: Fuzzy based intelligent relay selection and transition technique for delay tolerant networks. (22nd February 2022) - Sonkar, Nidhi; Pandey, Sudhakar; Kumar, Sanjay
Summary: Delay tolerant network (DTN) has attracted significant attention of the researchers due to its capability of delivering the message even in the situation where network connectivity is irregular. Irregular networks result in non‐delivery of data to user at right time, and the same is not possible with traditional algorithms due to requirement of end‐to‐end connectivity between nodes. DTN uses story–carry–forward technique to deliver a message in the environment of disconnection. Hence, for message transmission from source node to destination node, a relay node or forwarder node is required. The efficiency of the network is mainly dependent on the selection of forwarder node. Hence, forwarder node selection is very crucial in DTNs. The objective of this paper is to propose an efficient relay node selection technique integrated with fuzzy logic, based on four properties of node, namely, number of encounters, residual energy, buffer capacity, and speed so that performance metrics of the network can be improve. Proposed method uses fuzzy logic to decide which node should be selected as relay node in multi hop strategy. The study of simulation results indicate that proposed algorithm improves performance of the network with regards to delivery ratio, delay, hop count, and throughput. Abstract : In this paper, a fuzzy logic‐based relay node selection technique is proposed, which includes four input parameters and a single output parameter ("Grade"). Fuzzy logic system calculates the value of "Grade" for each node, which comes in the communication range. At the source node, the node which has the highest value of "Grade" will be selected as relay node. Further, at intermediate node, the message will transfer only if the difference between "Grade" value is greater than or equal to 50%.